Mechanism of copper nanoparticle toxicity in rainbow trout olfactory mucosa. (1st September 2021) - Razmara, Parastoo; Imbery, Jacob J.; Koide, Emily; Helbing, Caren C.; Wiseman, Steve B.; Gauthier, Patrick T.; Bray, Douglas F.; Needham, Maurice; Haight, Travis; Zovoilis, Athanasios; Pyle, Gregory G.
Abstract: Chemosensory perception is crucial for fish reproduction and survival. Direct contact of olfactory neuroepithelium to the surrounding environment makes it vulnerable to contaminants in aquatic ecosystems. Copper nanoparticles (CuNPs), which are increasingly used in commercial and domestic applications due their exceptional properties, can impair fish olfactory function. However, the molecular events underlying olfactory toxicity of CuNPs are largely unexplored. Our results suggested that CuNPs were bioavailable to olfactory mucosal cells. Using RNA-seq, we compared the effect of CuNPs and copper ions (Cu 2+ ) on gene transcript profiles of rainbow trout ( Oncorhynchus mykiss ) olfactory mucosa. The narrow overlap in differential gene expression between the CuNP- and Cu 2+ -exposed fish revealed that these two contaminants exert their effects through distinct mechanisms. We propose a transcript-based conceptual model that shows that olfactory signal transduction, calcium homeostasis, and synaptic vesicular signaling were affected by CuNPs in the olfactory sensory neurons (OSNs). Neuroregenerative pathways were also impaired by CuNPs. In contrast, Cu 2+ did not induce toxicity pathways and rather upregulated regeneration pathways. Both Cu treatments reduced immune system pathway transcripts. However, suppression of transcripts that were associated with inflammatory signaling was only observed with CuNPs. Neither oxidative stress nor apoptosis were triggered by Cu 2+ or CuNPs in mucosal cells. Dysregulation of transcripts that regulate function, maintenance, and reestablishment of damaged olfactory mucosa represents critical mechanisms of toxicity of CuNPs. The loss of olfaction by CuNPs may impact survival of rainbow trout and impose an ecological risk to fish populations in contaminated environments. Graphical abstract: Image 1 Highlights: Olfactory mucosa showed differential transcriptome responses to nano and soluble Cu. Odorant reception and neuroregeneration transcripts were downregulated by nano Cu. In the soluble Cu-exposed fish, neuroregeneration pathways were upregulated. Transcripts related to immune system were influenced by both by Cu contaminants. Oxidative stress and apoptosis were not induced by Cu contaminants in mucosal cells. Abstract : Our findings show that nano Cu operate through different mechanisms than Cu 2+ in the fish olfactory system, their effects are more severe leading to a lower likelihood of recovery.